Letter - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960
1940-03-30 038-0048-001 TELEPHONE: DUNKELD 34 EASTWOOD, DUNKELD. 30th March, 1940. H.V. Tewson, Esq., Transport House, Smith Square, London, S.W.1. Dear Mr Tewson Will you forgive my writing to ask, as I do at the request of the Basque Children's Committee, whether you could let the Committee have any of the balance of the £1,000 which you thought some time ago would be forthcoming for the children. You sent us £300 a month or two ago, which was very helpful, but our funds have been terribly depleted by the costs of repatriation and by the dilapidation bills which are now coming in from some of the homes which have been vacated. I enclose a statement showing that there is not sufficient in the repatriation fund to pay for the cost of the repatriations made to date, and a statement for the week ending 22nd March, which shows the big hole one dilapidation cost has made in our maintenance funds. There is now only a balance of £216, and we have to meet maintenance charges of about £90, in addition to office charges. These have been swollen this last week by the Telephone Account, which I assume is for the quarter. I hope and believe that the Telephone Account is now a good deal less than formerly, as one or two members of the staff who were not sufficiently careful have left, and Dr.Camps is keeping a strict eye on Trunk calls. These, [however] in any case dwindle with the dwindling of the Homes. Our expenses for the Basque Children anyway are over £100 a week; and I am afraid that the Appeal I have been signing during my stay in London is bringing in very little. On the other hand we have £150 coming in from S.E.R.E., and Dr. Camps thinks that the International Commission have still £100 to send us. Miss Pye has also suggested to Dr. Camps that Mr. Kershener of the American Commission might be ready to consider the possibility of caring in France for the 160 of our children whose families are already there. She has written to ask him about this. But/ 292/946/38/48(I)